Analisis Refering Expression Dalam Cerpen The Deer and The Crocodile Karya Sindu Ann - Ulfayanti, Ulfayanti; Mujahid, Ayinun; Fauzi, Ahmad; Alfiani, Putri Nuraura; Aminah, Sitti; Harmilawati, Harmilawati (Lontara Digitech Indonesia, 2024)
Referring expression is a form of language used to refer to or identify an object, person, or concept in the context of conversation or writing. This research analyzes the use of referring expressions in the short story